The Generic Short Patient Experiences Questionnaire (GS-PEQ): identification of core items from a survey in Norway - Olsen Rolf; Bjertnaes Oyvind A; Sjetne Ingeborg; Iversen Hilde; Bukholm Geir (BMC, 2011)
Abstract Background Questionnaires are commonly used to collect patient, or user, experiences with health care encounters; however, their adaption to specific target groups limits comparison between groups. We present the construction of a generic questionnaire (maximum of ten questions) for user evaluation across a range of health care services. Methods Based on previous testing of six group-specific questionnaires, we first constructed a generic questionnaire with 23 items related to user experiences. All questions included a "not applicable" response option, as well as a follow-up question about the item's importance. Nine user groups from one health trust were surveyed. Seven groups received questionnaires by mail and two by personal distribution. Selection of core questions was based on three criteria: applicability (proportion "not applicable"), importance (mean scores on follow-up questions), and comprehensiveness (content coverage, maximum two items per dimension). Results 1324 questionnaires were returned providing subsample sizes ranging from 52 to 323. Ten questions were excluded because the proportion of "not applicable" responses exceeded 20% in at least one user group. The number of remaining items was reduced to ten by applying the two other criteria. The final short questionnaire included items on outcome (2), clinician services (2), user involvement (2), incorrect treatment (1), information (1), organisation (1), and accessibility (1). Conclusion The Generic Short Patient Experiences Questionnaire (GS-PEQ) is a short, generic set of questions on user experiences with specialist health care that covers important topics for a range of groups. It can be used alone or with other instruments in quality assessment or in research. The psychometric properties and the relevance of the GS-PEQ in other health care settings and countries need further evaluation.